THE ROLE OF PUSPITA BAHARI AS A COMMUNITY BASED ORGANIZATION IN EMPOWERING FISHERMAN WOMEN (Study: Women Fishermen in Morodemak Village, Bonang District, Demak Regency) - Prihatiningsih, Tutut Ayu; Astuti, Puji (Journal of Politic and Government Studies, 2019)
Community Based Organizations (OBK) have a focus on service in their respective fields in accordance with the organization's vision and mission. One of them is focusing on empowerment. Likewise with Puspita Bahari as the only Community-Based Organization in Demak District that empowered women fishermen in the coastal area of Bonang Subdistrict, Morodemak Village. This study aims to find out how Puspita Bahari works and the success of empowering women fishermen and how the Puspita Bahari organization is sustainable in empowering women fishermen. The research method used is descriptive qualitative with data collection techniques in the form of observation, interviews and documentation. The data obtained is then analyzed by triangulating data sources.The results of the research show that the workings of Puspita Bahari as a community-based organization are carried out through economic empowerment, psychological empowerment, legal empowerment and connecting them to government or network institutions. This was done not only from Puspita Bahari itself but together with the organization's network. Fishermen processing sea fish catchers empowered by Puspita Bahari can be said to have succeeded, but fishermen fishing women in the sea have not been able to say they are successful because they do not have productive economic businesses. They focus on empowerment which fights for their rights as fishermen fishing women in the sea. Organizational sustainability efforts are carried out internally through regeneration and recruiting young cadres to be able to continue the program or activities of the organization besides that there is also a coordinator in the three villages in the scope of empowerment. Externally that is building strong relationships with informal networks (community) / fishermen women, but Puspita Bahari does not build strong relationships with community leaders and religious leaders. Puspita Bahari builds strong relationships with local or national networks or organizations to partner.Keywords: Puspita Bahari, empowerment, fishermen women.